Diagnóstico da gestão dos processos de contratações emergenciais celebradas sob o regime da flexibilização temporária promovida pela Lei nº 13.979/2020 durante a pandemia de covid-19 na Secretaria de Estado da Saúde de Goiás - Hurbano, Paulo André Teixeira (2023)
The dissertation presents a diagnosis about the management of public emergency contracts in Department of Health of Goiás State during the COVID-19 crisis, negotiated by the regulation of Law nº 13.979/2020. The objective is to investigate the variables of duration (time) of these processes, regularity of their post-award phase and prices of their contracted goods and services. It was verified a possible correlation between the results of these variables and the flexibilities promoted by the temporary and exceptional Law. After testing the research hypotheses, it is examined the control mechanisms used in such processes. The study suggests propositions for the future based on the experiences acquired with the contractual management scenario under an emergency ando flexible legal regime.